The Uses Of Memoirs And Oral History Works In Researching The 1965–1966 Political Violence In Indonesia - Hearman, Vannessa (Penerbit Universiti Sains Malaysia (USM Press), 2009)
Since the end of Suharto's rule in 1998, Indonesia's official history has been contested, especially by former political prisoners from the 1965 period, who had previously been regarded as the regime's enemies. In challenging the New Order regime's historical accounts, these former prisoners have written, and in some instances published, their memoirs, as well as taken part in oral history projects. This paper examines the genre of 'prisoner memoirs' and oral history work, which have flourished in the post-Suharto period. It surveys some of the common themes and motivations among such works and draws upon interviews with expolitical prisoners engaged in both memoir-writing and oral history projects. The paper also charts how such a genre and method can assist with documenting more of Indonesia's post-independence period from a diverse range of sources. Writing on Indonesia's post-independence history has posed many difficulties due to the New Order regime's representation of the Sukarno period as constituting a 'political mistake'. The end of the Cold War, however, has generated more interest among scholars in how Southeast Asian leftist movements and organisations dealt with questions of ideology and mobilisation in the nation-building phase of the 1950s and 1960s.